2005
DOI: 10.1021/ma051923n
|View full text |Cite
|
Sign up to set email alerts
|

Influence of PMMA-Chain-End Tethered Polyhedral Oligomeric Silsesquioxanes on the Miscibility and Specific Interaction with Phenolic Blends

Abstract: Two different molecular weights of poly(methyl methacrylate) (PMMA) and PMMA containing polyhedral oligomeric silsesquioxane (PMMA-POSS) homopolymers have been prepared via the atom transfer radical polymerization (ATRP) technique. The miscibility and specific interaction behaviors of PMMA-POSS and PMMA with phenolic resin were investigated by differential scanning calorimetry and Fourier transform infrared spectroscopy (FTIR). FTIR results reveal that at least three competing equilibriums are present in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(68 citation statements)
references
References 46 publications
2
64
1
1
Order By: Relevance
“…Phenolic/PMMA systems are also miscible blends that have been studied extensively [24,25]. In a previous study, we determined a value of K A of 20 directly through a least-squares fitting procedure based on the fraction of hydrogen-bonded C=O groups measured experimentally in a binary phenolic/PMMA blend [25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenolic/PMMA systems are also miscible blends that have been studied extensively [24,25]. In a previous study, we determined a value of K A of 20 directly through a least-squares fitting procedure based on the fraction of hydrogen-bonded C=O groups measured experimentally in a binary phenolic/PMMA blend [25].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we determined a value of K A of 20 directly through a least-squares fitting procedure based on the fraction of hydrogen-bonded C=O groups measured experimentally in a binary phenolic/PMMA blend [25]. We also used atom transfer radical polymerization (ATRP) to prepare inorganic/organic polymer hybrids featuring polyhedral oligomeric silsesquioxane (POSS) moieties at the chain ends; we obtained well-defined PMMA and PMMA-POSS homopolymers with designed molecular weights (ca.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an index of crystallinity, (I t -I 0 )/(I " -I 0 ) is used to define the relative light intensity, where I t and I 0 are the I value at time t c = t and 0, respectively, I " is the I value when it levels off. Figure 7 shows the typical (I t -I 0 )/(I " -I 0 ) changes with t c for PLLA/PLLA-OPOSS 30 films, where the starting, half, and ending times for overall PLLA/PLLA-OPOSS 30 crystallization [t c (S), t c (1/2), and t c (E), respectively] are defined. Figure 8 plotted the evaluated t c (S), t c (1/2), and t c (E) as a function of T c .…”
Section: Dynamic Isothermal Crystallizationmentioning
confidence: 99%
“…POSS molecules can be easily incorporated into polymer systems through blending, grafting or copolymerization [15,16]. For example, several polymers, such as HDPE [21], PP [22], epoxy [23][24][25][26], PMMA [27][28][29][30], PU [31,32], PET [33][34][35] and PC [36], have been blended with POSS. It has been reported that PLLA/POSS nanocomposites have enhanced crystallization rate, improved mechanical properties and accelerated hydrolytic degradation as compared with pristine PLLA [19].…”
Section: Introductionmentioning
confidence: 99%